Peran Pendidikan Agama Kristen dalam Menanamkan Nilai-nilai Kekristenan di Sekolah Dasar susukan 07 Jakarta Timur - Imelda Meyvita; Yulinar Maharani Agetta (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Christian Religious Education (CRE) in elementary schools plays a strategic role in fostering students' faith and moral values from an early age. This study aims to describe and analyze the role of CRE in spiritual growth and character development by highlighting the implementation of Christian values in classroom practices. The research employs a qualitative approach with a descriptive design. Data were collected through direct classroom observations and in-depth interviews with teachers and upper-grade students (grades 4–6) at an elementary school in East Jakarta that has adopted the Merdeka Curriculum. The findings reveal that CRE significantly contributes to shaping student attitudes such as love, responsibility, honesty, and forgiveness. Teachers play a central role in contextualizing these values through relevant and meaningful learning strategies. Challenges include limited instructional time, student diversity, and the need for strengthened pedagogical and spiritual competence. These results underscore the importance of support from schools and parents to implement inclusive and impactful CRE aligned with the Merdeka Curriculum's values.